2022
DOI: 10.5114/ada.2020.101637
|View full text |Cite
|
Sign up to set email alerts
|

Etiopathogenesis of dermatitis herpetiformis.

Abstract: Dermatitis herpetiformis is a rare chronic, autoimmune bullous disease linked to gluten sensitivity with intense pruritus and characteristic skin eruptions. Etiopathogenesis is complex and not fully understood. It is currently considered to be a specific cutaneous manifestation of celiac disease. Genetic, environmental and immunological factors influence both conditions. Exposure to gluten is the starting point of an inflammatory cascade leading to the formation of circulating IgA antibodies against tissue tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…Given the fact that adalimumab inhibits TNF-alpha, it makes the development of DH a puzzling phenomenon, as earlier research has indicated that the activation of cutaneous endothelial skin cells was associated with increased serum levels of TNF-alpha. However, as knowledge has accumulated over the last two decades, it was apparent that etiopathogenesis of DH is quite complex and involves a wide range of intricate immunological reactions, which starts with the binding of epidermal antibodies and IgA transglutaminases, leading ultimately to matrix metalloproteinases release, inflammatory cytokine production, and neutrophil influx [ 10 ]. It is thus difficult to evaluate how adalimumab exactly affects this cascade of events, eventually leading to full-blown DH presentation.…”
Section: Discussionmentioning
confidence: 99%
“…Given the fact that adalimumab inhibits TNF-alpha, it makes the development of DH a puzzling phenomenon, as earlier research has indicated that the activation of cutaneous endothelial skin cells was associated with increased serum levels of TNF-alpha. However, as knowledge has accumulated over the last two decades, it was apparent that etiopathogenesis of DH is quite complex and involves a wide range of intricate immunological reactions, which starts with the binding of epidermal antibodies and IgA transglutaminases, leading ultimately to matrix metalloproteinases release, inflammatory cytokine production, and neutrophil influx [ 10 ]. It is thus difficult to evaluate how adalimumab exactly affects this cascade of events, eventually leading to full-blown DH presentation.…”
Section: Discussionmentioning
confidence: 99%
“…Dermatitis herpetiformis (Duhring's disease, DH) is a chronic autoimmune, blistering cutaneous condition characterized by polymorphic lesions such as vesicles, erosions, erythematous patches, urticaria and nodules [1][2][3][4][5][6], that are usually found symmetrically on the extensor surfaces of the limbs, buttocks, and neck [2,[4][5][6][7][8][9][10][11][12]. These lesions are accompanied by intense itching of the skin [2,4,[10][11][12][13][14]. DH occurs with an asymptomatic sensitivity to gluten that is contained in wheat, oats, barley, and rye grains [1,3,6,[14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…These lesions are accompanied by intense itching of the skin [2,4,[10][11][12][13][14]. DH occurs with an asymptomatic sensitivity to gluten that is contained in wheat, oats, barley, and rye grains [1,3,6,[14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…4 JAK3 seems to be the most expressed in these patients, although JAK2 and, to a lesser extent, JAK1 may also be overexpressed. The inhibition of proinflammatory signaling cytokines such as IL-6 (binds to JAK1 and JAK2 receptors), IL-8 (increased in the basal epidermal layer, and involved in the chemotaxis and activation of neutrophils mainly through JAK2 receptors), IL-12 (elevated in serum, lesional, and perilesional skin, 3 participates in the activation and differentiation of T cells through JAK2/TYK2 receptors), or IL-31 (associated with chronic skin inflammation and pruritus in allergic diseases by activating JAK 1 and JAK2 signaling molecules) could justify the benefits of JAK inhibitors in this disease. Baricitinib, along with tofacitinib, have been considered the least selective JAK inhibitors, therefore offering an interesting therapeutic approach for these patients.…”
mentioning
confidence: 99%
“…They both present Th2 cytokine profiles in active phases and, despite serum concentration of IL-31 having been reported to be lower than controls in patients with DH, 2 it is significantly overexpressed in the skin. 3 The JAK-STAT signaling pathway has also significantly enhanced DH, presumably in the context of the proinflammatory cytokine network and infiltrate in tissues. 4 JAK3 seems to be the most expressed in these patients, although JAK2 and, to a lesser extent, JAK1 may also be overexpressed.…”
mentioning
confidence: 99%